2015
DOI: 10.1007/s12274-015-0900-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of defect formation in chemically vapor deposited (CVD) graphene during laser irradiation: The case of Raman investigation

Abstract: The effects of laser irradiation on Chemically Vapor Deposited graphene is studied by analyzing the temporal evolution of Raman spectra acquired under different illumination conditions. It is observed that the normalized intensity of the defect-related peak increases with the square root of the time of exposure, in a nearly linear way with the laser power density and that the hardness of graphene to the radiation damage depends on its intrinsic structural quality. The results suggest that, contrarily to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…2b ) . We find an asymmetric distribution of I D /I G ratios with a tail towards higher defectiveness that had been previously attributed to the modification of metastable bonds in graphene under laser irradiation during mapping 18 22 . It had been suggested that the observed defect distribution is a product of the original defect concentration and a time-dependent increase in defect concentration during Raman mapping.…”
Section: Resultssupporting
confidence: 61%
“…2b ) . We find an asymmetric distribution of I D /I G ratios with a tail towards higher defectiveness that had been previously attributed to the modification of metastable bonds in graphene under laser irradiation during mapping 18 22 . It had been suggested that the observed defect distribution is a product of the original defect concentration and a time-dependent increase in defect concentration during Raman mapping.…”
Section: Resultssupporting
confidence: 61%
“…The laser‐irradiation step, as depicted in Figure a, was carried out using a continuous‐wave (CW) laser with a wavelength of 514 nm, which is below the reported ablation threshold for graphene and is in the spectral range where the Au thin film is highly reflective and optically nonabsorbent, in order to avoid damage to the electrodes . The fluence was set at 6.24 × 10 9 J cm −2 , which is higher than the threshold value for the sp 2 CC bond breaking . Since the photon energy of the laser is lower than the binding energy of graphene, the disassembly of these bonds occurs mainly due to the recombination of the photogenerated electron–hole pairs during intense illumination of graphene .…”
Section: Resultsmentioning
confidence: 99%
“…The fluence was set at 6.24 × 10 9 J cm −2 , which is higher than the threshold value for the sp 2 CC bond breaking . Since the photon energy of the laser is lower than the binding energy of graphene, the disassembly of these bonds occurs mainly due to the recombination of the photogenerated electron–hole pairs during intense illumination of graphene . Bonds between the open‐ended C atoms and metal atoms are then feasible through a thermal annealing step .…”
Section: Resultsmentioning
confidence: 99%
“…Micro-Raman analysis has been performed in a homemade system [ 21 , 22 ]. All acquisitions of Raman spectra were performed with a laser (λ = 532 nm, wavelength) spot diameter of 1 µm and power of P ≈ 2 mW.…”
Section: Methodsmentioning
confidence: 99%